2009
DOI: 10.1016/j.jtbi.2009.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Why are cellular switches Boolean? General conditions for multistable genetic circuits

Abstract: The logic of cellular decision making is largely controlled by regulatory circuits defining molecular switches. Such switching elements allow to turn a graded input signal into an all-or-nothing output. Traditional studies have focused on this bistable picture of regulation, but higher-order scenarios involving tristable and tetrastable states are possible too. Are these multiswitches allowed in simple gene regulatory networks? Are they likely to be observed? If not, why not? In this paper we present the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
(33 reference statements)
0
34
0
Order By: Relevance
“…The theoretical solution of introducing nonlinearity ARTICLE into a system composed of monomeric DNA-binding elements proposed the introduction of a pair of hypothetical transcription factors, each of which should be able to activate its own expression and simultaneously repress the transcription of the opposing transcription factor 29,30 . Such types of transcription factors would be very difficult to design.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical solution of introducing nonlinearity ARTICLE into a system composed of monomeric DNA-binding elements proposed the introduction of a pair of hypothetical transcription factors, each of which should be able to activate its own expression and simultaneously repress the transcription of the opposing transcription factor 29,30 . Such types of transcription factors would be very difficult to design.…”
Section: Resultsmentioning
confidence: 99%
“…The realization that mutually inhibiting TF-TF switches and mutually inhibiting miR-TF chimeric switches play an important role in cell-fate determination has led several groups to conduct theoretical studies of such circuits (17)(18)(19)(20)(21)(22). These studies have revealed that inclusion of transcription selfactivation can lead to the coexistence of three stable states (tristability) (17)(18)(19)(20). More specifically, the classical TF-TF toggle switch has two stable states, (0,1) and (1,0), where state (0) corresponds to relatively low expression (low concentration) and state (1) corresponds to relatively high expression (23).…”
Section: Significancementioning
confidence: 99%
“…3A). Typically, self-activation on both sides of the toggle switch can render the circuit tristable (ternary or three-way) switch (52)(53)(54)(55). However, self-activation on one side can also render the circuit tristable for a wide range of parameters, as seen in both TF-TF toggle switches and miRNA-TF chimera toggle switches (36).…”
Section: The Unit Modulesmentioning
confidence: 99%